2020
DOI: 10.2340/00015555-3449
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic and Immunohistochemical Observations in Anetodermic Pilomatricoma: A Case Report

Abstract: Fig. 1. Clinical and dermoscopic presentation of anetodermic pilomatricoma. (a) A protuberant nodule with bluish-reddish soft-wrinkled surface on the left arm. (b) Dermoscopy showing a bluish-greyish and yellowish-white central area with blurred linear-irregular vessels and reddish border (original magnification ×30).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Such lesions can be ulcerated or non-ulcerated and may exhibit variable pigmentation with combinations of blue-gray, red, and white/yellow colors [ 4 , 6 8 , 10 , 12 14 ]. Additionally, atypical pilomatricomas with an anetodermic appearance have also been reported [ 5 , 9 , 11 ]. In the literature, ultrasound was used to confirm, support or exclude the diagnosis of pilomatricoma [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such lesions can be ulcerated or non-ulcerated and may exhibit variable pigmentation with combinations of blue-gray, red, and white/yellow colors [ 4 , 6 8 , 10 , 12 14 ]. Additionally, atypical pilomatricomas with an anetodermic appearance have also been reported [ 5 , 9 , 11 ]. In the literature, ultrasound was used to confirm, support or exclude the diagnosis of pilomatricoma [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tricolor appearance could be considered as a dermoscopic clue to make the diagnosis. In this regard, several authors reported typical pilomatricomas characterized by a bi- or tricolor nodular aspect at dermoscopy [ 3 6 , 9 , 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical types of the tumor include familial, perforating, multinodular [ 5 ], exophytic, anetodermic, and giant PM [ 6 ]. The bullous type is seen in only 3 to 6% of cases [ 7 ]. It is seen more frequently in women and children, and often occurs on the shoulders and upper arms.…”
Section: Discussionmentioning
confidence: 99%
“…Acanthosis and increased basal pigmentation in the overlying epidermis also contribute to the bluish rim. 5 Vascular structures (telangiectasias) and reddish homogenous areas correspond to the vascular dilation and haemorrhages, which are distinctly visible due to loss of dermal connective tissue. 6 Another distinct dermoscopic finding was the presence of shiny white streaks on polarised light, which was due to altered collagen in the underlying dermis.…”
Section: Casementioning
confidence: 99%
“…The white areas were invariably surrounded by a bluish rim, which represent the pigmentation within the tumour cells or dermal melanophages. Acanthosis and increased basal pigmentation in the overlying epidermis also contribute to the bluish rim 5 . Vascular structures (telangiectasias) and reddish homogenous areas correspond to the vascular dilation and haemorrhages, which are distinctly visible due to loss of dermal connective tissue 6 .…”
Section: Casementioning
confidence: 99%